Pharmacodynamic considerations in bioequivalence assessment: comparison of novel and existing metrics - Karalis, V.; Macheras, P. (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 2003)
This study addresses the utility of pharmacodynamic considerations to the assessment of bioequivalence (BE) studies. A novel methodology was developed and the performance of classic, nonclassic and novel BE indices was evaluated using extensive simulations of BE trials generated from a classic pharmacokinetic (PK)/pharmacodynamic (PD) model. Three novel indices based on drug's pharmacodynamics were developed and served as criteria for the assessment of all BE indices. Modified power curves were constructed and used for the analysis of BE trials from a PD point of view. All BE indices of either purely PK or PD nature were classified in a semiquantitative manner according to their strictness in declaring BE. The partial area until the peak concentration followed by the two newly proposed metrics (MARD, MARD(w1)) exhibited the most strict performance in declaring BE irrespective of the PK scenarios examined. The study opens new avenues in BE assessment since it places more emphasis on the PD aspects of the formulations. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: bioequivalence; direct curve comparison metrics; pharmacodynamics; simulated trials